Eksistensi Divisi Marketing Communication dalam Menjalankan Fungsi Public Relations di E-commerce AladinMall by Mister Aladin - Ade Maulida; Sa’diyah El Adawiyah (Institut Nalanda, 2024)
AladinMall by Mister Aladin is an e-commerce newcomer owned by the largest media company, namely the MNC group, which was founded at the end of 2021. As an e-commerce newcomer, the existence of public relations is needed by AladinMall by Mister Aladin to become a communication bridge between the company's internal external to the company. AladinMall by Mister Aladin in its structure does not yet have a public relations division because the scope of the company is still very small, however, the public relations function at AladinMall by Mister Aladin is still carried out, only this function is carried out by the Marketing Communications & Strategy division. In relation to this, this research aims to determine the existence of the Marketing Communication division in carrying out the public relations function in e-commerce AladinMall by Mister Aladin and to determine the public relations activities carried out by the Marketing Communication division of AladinMall by Mister Aladin. The approach used in this research uses a qualitative approach, the data collection technique used is interviews with the Marketing Communication division which carries out the public relations function at AladinMall by Mister Aladin. The collected data is then subjected to data reduction, data presentation and conclusion drawing. The results of the research show that the existence of a marketing communications division in carrying out the public relations function in e-commerce AladinMall by Mister Aladin is carried out by carrying out public relations activities such as online and offline events, partnerships with various brands, making press releases, contributing to social or CSR activities. , and carrying out the public relations function which includes serving the public interest (it should serve the public interest), maintaining good relationships (maintain good communication) and emphasizing good ethics and behavior (stress good morals and manners).